Blood pressure tracking as an indicator of hypertension risk - Zulkifli, S.N. (Stamford Publishing Pte Ltd / Singapore Medical Association, 1992)
The significance of high blood pressure to cardio- and cerebrovascular disease is well recognized. The associated mortality and morbidity risks call for multiple approaches to control the development of high blood pressure. Recent studies have shown that precursors of cardiovascular disorders may be apparent from a young age, and that these can persist and contribute to disease in later life. With regard to blood pressure, the phenomenon of persisting at the same rank has been referred to as tracking. This allows for the possible identification of high-risk groups, for whom early intervention can be initiated. In this paper, some of the findings of studies on blood pressure tracking are reviewed.